ANALYSIS OF THE UTILIZATION OF THE HARBOR AREA AT THE PORT OF TANJUNG PERAK - Renta Novaliana Siahaan; Sereati Hasugian; Faris Nofandi; Alwi Sina Khaqiqi; Rizki Adi Pratama (Meteor STIP Marunda, 2024)
Tanjung Perak Port is the initial gateway to Surabaya which handles more than 40% of international goods trade. In this case, the Kertosusilo Gate Area (GKS) has a very important position with its sea area having the busiest shipping lanes in Indonesia with 15,409 vessels operating at the end of 2021. The dense distribution of port activities in sea transportation creates complex problems which impact on delays in cargo delivery in Tanjung Perak Harbor. Problems that arise include sedimentation due to the construction of the Maspion Indonesia Port terminal, narrowing of sea water and changes in sea area which causes narrowing of the Madura Strait sea area, as well as complaints from port users regarding shipping lanes, anchoring areas in terms of depth, area, Vessel Traffic Services (VTS), services. ship guidance and security. Based on these problems, research was carried out on the utilization and needs of the anchorage area at Tanjung Perak Port. Starting with conducting research preparation, collecting data by compiling data related to the general picture of economic growth, especially in the East Java region as well as operational technicalities and conditions of the Tanjung Perak port. So that we can obtain the results of utilization research for a docking area capacity of 20,330 ships per year with a utility value of the docking area at Tanjung Perak Port of 73.5%.